STRATEGIC ANALYSIS OF PT. KMDS, TBK. (INDONESIA’S MONIN SYRUPS DISTRIBUTOR & IMPORTER) - Lukman, Steven; Maupa, Haris (Graduate Program of Universitas Tarumanagara, 2023)
This study aim to formulate strategy for PT. KMDS, Tbk. which will be started with identify the posision of the company in the market in order to know the competitive advanatge in the market. After established for more than 20 years PT. KMDS, Tbk. should improve accordingly with the growth of the market. Qualitative method will be used with purposive sampling & total of 16 samples will consist at least working in managerial position & working in sales department. The samples will be covering the scope of Java & Bali island as it was the biggest contributor of national sales for company. The instrument used in this research will be questionnaires formulated from the internal & external factor analysis strategy. The data gathered then will be processed using Strategic Position And Action Evaluation (SPACE) matrix combined with the SWOT matrix thus called SWOT quadrant analysis.The result shown that according to the samples respond, PT. KMDS, Tbk. does have big score both in the internal & external factor. Detailed explanation shown that company stregth overpower the weakness & opportunity also overpower the threat. Thus, it is concluded that the company posisition is at the 1st Quadrant which support for the aggressive strategy